3D SBF-SEM analysis of inner organization of unicellular protist cell - Salburg, Audra (Jihočeská univerzita, 2023)
A culture of a unicellular protist Diplonema japonicum was imaged with a Serial Blockface Scanning Electron Microscope and the resulting images were further processed with the Microscopy Image Browser program. From the obtained images the whole ultrastructure of various cells was analysed and the relationship between the cells mitochondria and endosymbionts was investigated. In addition a 3D model based on the resulting images of a D. japonicum cell is constructed to visualise potential endosymbionts residing inside the mitochondria.
3D SBF-SEM analysis of inner organization of unicellular protist cell
Keywords: D. Japonicum; diplonemids; endosymbiosis; electron microscopy; ultrastructure; protist; holosporaceae; D. Japonicum; diplonemids; endosymbiosis; electron microscopy; ultrastructure; protist; Holosporaceae